Relationship between Helicobacter pylori babA2 status with gastric epithelial cell turnover and premalignant gastric lesions. Issue 4 (1st October 2002) - Yu, J; Leung, W K; Go, M Y Y; Chan, M C W; To, K F; Ng, E K W; Chan, F K L; Ling, T K W; Chung, S C S; Sung, J J Y
Abstract : Background: Helicobacter pylori blood group antigen binding adhesin (BabA) mediates bacterial adherence to human blood group antigens on gastric epithelium. Although strains harbouring babA2 were recently found to be associated with peptic ulcer and gastric cancer, the role of bab A2 in cellular turnover, severity of gastritis, and premalignant changes is poorly understood. Aim: We correlated H pylori babA2, vacuolating toxin ( vacA ), and cytotoxin associated gene A ( cagA ) genotypes with the severity of gastric inflammation and epithelial cell turnover in a group of Chinese patients from an area with a high incidence of gastric cancer. Patients and methods: H pylori isolates were obtained from 104 Chinese patients who participated in a gastric cancer prevention programme. Genotype variants of babA2, vacA, and cagA were determined by polymerase chain reaction. Antrum and corpus histopathology was examined according to the updated Sydney classification. Apoptosis was scored by terminal uridine deoxynucleotidyl nick end labeling (TUNEL) and proliferation by Ki-67 immunostaining. Results: Of the 104 patients, 102 (98.1%) harboured cagA + strains and all had vacA s1 genotype. The babA2 + strains were found in 83 (79.8%) patients and were associated with higher lymphocytic infiltration (p=0.028), presence of glandular atrophy (odds ratio (OR) 7.5, 95% confidence interval (CI) 2.3–24.3), and intestinal metaplasia (OR 7.4, 95% CI 2.2–25.3) in the antrum. Increased epithelial proliferation was also noted in individuals infected with babA2 + strains (p=0.025). Strains harbouring cagA + / vacA s1 genotypes lacked this association in the absence of babA2 . Conclusions: The presence of babA2 + H pylori strains alone or in combination with cagA + and vacA s1 was associated with the presence of preneoplastic gastric lesions.